Method for synthesizing Fe-BDC microwave catalyst through microwave solvothermal method and application of Fe-BDC microwave catalyst

By adding acetate ions to the aqueous NaAc solution to regulate the reaction environment, forming a defective structure, improving the catalytic activity and stability of the Fe-BDC microwave catalyst, solving the problem of insufficient microwave catalytic performance in the prior art, and achieving efficient degradation of organic pollutants in wastewater.

CN119708519AActive Publication Date: 2025-03-28DALIAN MARITIME UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411843048.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

In the prior art, microwave catalytic performance is insufficient, resulting in low activity and efficiency of the catalyst.

Method used

The Fe-BDC microwave catalyst was synthesized by microwave solvothermal method. By adding acetate ions to the aqueous NaAc solution, the reaction environment was adjusted and the defective structure in the catalyst was formed, thereby improving the catalytic activity.

Benefits of technology

The catalytic activity and stability of Fe-BDC microwave catalysts are improved, and their ability to degrade organic pollutants in wastewater under microwave irradiation is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708519A_ABST
    Figure CN119708519A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of microwave catalysis, and particularly relates to a method for synthesizing a Fe-BDC microwave catalyst through a microwave solvothermal method and application of the Fe-BDC microwave catalyst. The method comprises the following steps: (1) dissolving terephthalic acid in a NaAc aqueous solution to obtain a solution A; (2) dissolving ferric salt in a NaAc aqueous solution to obtain a solution B; (3) dropwise adding the solution B into the solution A under a stirring condition; (4) under a stirring condition, carrying out microwave irradiation treatment on the mixed solution obtained in the step (3); and (5) filtering, collecting precipitates, washing and drying to obtain the Fe-BDC microwave catalyst. Sodium acetate (NaAc) is adopted to regulate and control the complexing effect of H2BDC and iron, so that the coordination efficiency is improved, the Fe-BDC which is regulated and controlled to have relatively high catalytic site content is promoted, the catalytic activity of the Fe-BDC is improved, a solvent in the synthesis process is a non-corrosive and non-toxic substance, and the method is green, energy-saving and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microwave catalysis, and specifically relates to a method for synthesizing a Fe-BDC microwave catalyst by a microwave solvent thermal method and application thereof. Background Art

[0002] Metal-organic frameworks (MOFs) are a new type of porous material. The metal centers separated by organic ligands can be regarded as quantum dots, which have unique electronic, optical and catalytic properties. MOFs materials mainly promote redox reactions with the help of a large number of active sites. Iron-based MOFs contain iron and organic carbon, which have the basic elements and structures required for microwave catalysts. They are viable catalysts due to their low cost, easy preparation and green environmental protection. Fe-BDC, as a typical iron-based MOFs, is a crystal structure formed by the combination of Fe3-μ3-oxo clusters and terephthalic acid (H2BDC).

[0003] So far, many different methods have been developed to prepare iron-based MOFs materials, including solvothermal method, room temperature stirring co-precipitation method, microwave solvothermal synthesis method, electrochemical synthesis method, mechanochemical synthesis grinding, dry gel conversion, template orientation, etc. The most commonly used method is the solvothermal method.

[0004] Microwave solvothermal synthesis is a green chemical synthesis method that uses microwave characteristics to accelerate chemical reactions. Compared with traditional solvothermal methods, microwaves can achieve rapid and uniform heating, improve the uniformity and crystal quality of the synthesized products, reduce the occurrence of side reactions, and have high product purity. Due to the increase in reaction rate, the synthesis process is accelerated, and the microwave solvothermal synthesis method can thus increase the overall yield of the product. Compared with traditional solvothermal methods, microwave solvothermal synthesis significantly reduces the large-scale use of solvents, thereby effectively avoiding possible environmental pollution and waste of resources. Therefore, microwave solvothermal synthesis technology has significant advantages in terms of time, energy efficiency, selectivity, etc. In addition, its products have the advantages of high crystal specific surface area, small size, large pore volume, strong adsorption capacity, low cost, and simple process, making it the preferred method for large-scale material synthesis in a short time. Summary of the invention

[0005] The purpose of the present invention is to provide a method and application of microwave solvent thermal synthesis of Fe-BDC microwave catalyst. The present invention uses NaAc as solvent, acetate ion (Ac - ) During the synthesis process, the reaction environment of the precursor is adjusted to promote the formation of defects in the product structure and improve the catalytic activity of the product. Under microwave irradiation, the defective Fe-BDC is conducive to exposing catalytic active sites and effective mass transfer, which can solve the problem of insufficient microwave catalytic performance in the prior art.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] The present invention provides a method for preparing a Fe-BDC microwave catalyst by microwave solvent thermal synthesis, the method comprising the following steps:

[0008] (1) dissolving terephthalic acid in a NaAc aqueous solution and performing sonication to obtain liquid A;

[0009] (2) dissolving the iron salt in the NaAc aqueous solution and stirring until all the iron salt is dissolved to obtain solution B;

[0010] (3) Add liquid B dropwise to liquid A under stirring;

[0011] (4) subjecting the mixed solution obtained in step (3) to microwave irradiation under stirring;

[0012] (5) Collect the precipitate by filtration, wash, and dry to obtain a Fe-BDC microwave catalyst.

[0013] In the above technical solution, preferably, in step (1), the concentration of the NaAc aqueous solution is 1 to 5 mol / L.

[0014] In the above technical solution, preferably, in step (2), the iron salt is any one of ferric chloride, ferric nitrate and ferric sulfate.

[0015] In the above technical solution, preferably, in step (3), the molar ratio of the iron element in the iron salt to terephthalic acid is 1:1 to 2:1.

[0016] In the above technical solution, preferably, in step (4), the power of the microwave irradiation is 320 to 640 W, and the time of the microwave irradiation is 1 to 60 min.

[0017] In the above technical solution, preferably, in step (5), washing is performed with deionized water and ethanol; the drying temperature is 40 to 90° C., and the drying time is 10 to 20 hours.

[0018] Another aspect of the present invention provides an application of the Fe-BDC microwave catalyst prepared by the above method in the degradation of organic pollutants in wastewater by microwave irradiation.

[0019] In the above technical solution, preferably, the application condition is: the microwave power is 80-800W.

[0020] The beneficial effects of the present invention are:

[0021] Another aspect of the present invention provides a microwave solvothermal Fe-BDC microwave catalyst prepared by the above preparation method, characterized in that the solvothermal reaction system is heated by microwave irradiation, which is a highly efficient and low energy consumption synthesis method. The catalyst activity formed by this method is higher than that of the traditional solvothermal method.

[0022] 1. The synthesis method of Fe-BDC microwave catalyst provided by the present invention uses NaAc as solvent, Ac - It can change the interaction between the reactants and the metal center, thereby affecting the crystal structure of the product. It can also form hydrogen bonds during synthesis, which helps the formation of defects. - Targeted adjustments can change the growth rate of the crystal, leading to defects, thus affecting the final catalytic performance. Moreover, acetic acid and acetates are non-corrosive and non-toxic substances, and are green, energy-saving and environmentally friendly when used in reactions.

[0023] 2. The present invention adopts microwave irradiation to heat the solvent thermal reaction system, which has the characteristics of high efficiency and low energy consumption. The stability, catalytic activity and other properties of Fe-BDC prepared by this synthesis method are greatly improved. 3. The catalyst of the present invention can be used for degradation of organic matter in wastewater under microwave induction. No additional reagents, such as oxidants such as hydrogen peroxide and persulfate, are needed to be added to the wastewater, and the catalyst exhibits good stability.

[0024] 4. The preparation method of the present invention is simple to operate, highly safe, low-cost, and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The activity comparison of Fe-BDC microwave catalyst samples prepared in Example 1 and Comparative Examples 1-2 in microwave degradation of tetracycline is shown;

[0026] Figure 2 The activity comparison of Fe-BDC microwave catalyst samples prepared in Example 1 and Comparative Examples 3 to 5 in microwave degradation of tetracycline is shown;

[0027] Figure 3 XRD patterns of Fe-BDC microwave catalyst samples prepared in Example 1 and Comparative Example 1;

[0028] Figure 4 FT-IR images of Fe-BDC microwave catalyst samples prepared in Example 1 and Comparative Example 1;

[0029] Figure 5 The activity comparison of Fe-BDC microwave catalyst samples prepared in Examples 1-3 in microwave degradation of tetracycline;

[0030] Figure 6The activity comparison of Fe-BDC microwave catalyst samples prepared in Examples 1 and 4 and Comparative Example 6 in microwave degradation of tetracycline is shown;

[0031] Figure 7 The activity comparison of Fe-BDC microwave catalyst samples prepared in Examples 1, 5, 6 and Comparative Example 7 in microwave degradation of tetracycline is shown;

[0032] Figure 8 The activity comparison of Fe-BDC microwave catalyst samples prepared in Examples 1, 7, 8 and Comparative Example 8 in microwave degradation of tetracycline is shown;

[0033] Fig. 9 The activity of the sample obtained in Example 1 in degrading tetracycline by microwave catalysis after repeated use. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.

[0036] Example 1

[0037] (1) Weigh 0.824 g of terephthalic acid (H2BDC) and add it to 20 mL of 1 mol / L NaAc. Ultrasonicate for 10 min to obtain solution A.

[0038] (2) Weigh 1.35 g of ferric chloride hexahydrate and add it to 10 mL of 1 mol / L NaAc. Ultrasonicate for 10 min to obtain solution B.

[0039] (3) Add liquid B dropwise to liquid A under stirring and continue stirring;

[0040] (4) Under stirring conditions, the mixed solution was placed in a microwave chemical reactor and subjected to microwave irradiation treatment at 480 W for 8 min;

[0041] (5) The precipitate was collected by filtration, washed with deionized water and ethanol, and dried at 70 °C for 18 h to obtain Fe-BDC.

[0042] Example 2

[0043] The Fe-BDC sample was prepared in a similar manner to that in Example 1, and the iron salt was 2.02 g of ferric nitrate nonahydrate.

[0044] Example 3

[0045] The Fe-BDC sample was prepared in a similar manner to that in Example 1, and the iron salt was 1.99 g of ferric sulfate.

[0046] Example 4

[0047] The Fe-BDC sample was prepared in a similar manner to that in Example 1, except that the amount of ligand terephthalic acid was 0.412 g.

[0048] Example 5

[0049] The Fe-BDC sample was prepared in a similar manner to that in Example 1, except that the concentration of the NaAc aqueous solution was 3 mol / L.

[0050] Example 6

[0051] The Fe-BDC sample was prepared in a similar manner to that in Example 1, except that the concentration of the NaAc aqueous solution was 5 mol / L.

[0052] Example 7

[0053] The Fe-BDC sample was prepared in a similar manner to that in Example 1, except that the microwave power was 320 W.

[0054] Example 8

[0055] The Fe-BDC sample was prepared in a similar manner to that in Example 1, except that the microwave power was 640 W.

[0056] Comparative Example 1

[0057] The Fe-BDC is prepared by a solvothermal method, comprising the following steps:

[0058] (1) Weigh 0.824 g of terephthalic acid (H2BDC) and dissolve it in 20 mL of 1 mol / L NaAc. Ultrasonicate for 10 min to obtain solution A.

[0059] (2) Weigh 1.35 g of ferric chloride hexahydrate, dissolve it in 10 mL of 1 mol / L NaAc, and sonicate for 10 min to obtain solution B;

[0060] (3) Under stirring conditions, slowly add solution B dropwise into the above solution A and continue stirring for 30 min;

[0061] (4) The mixed solution was transferred to a stainless steel reactor and reacted at 120°C for 15 h;

[0062] (5) After cooling to room temperature, the precipitate was collected by filtration, washed with deionized water and ethanol, and dried at 70°C for 18 h to obtain Fe-BDC.

[0063] Comparative Example 2

[0064] Fe-BDC was prepared by the room temperature stirring co-precipitation method. The specific steps are as follows:

[0065] (1) Weigh 0.824 g of terephthalic acid (H2BDC) and dissolve it in 20 mL of 1 mol / L NaAc reaction solvent, and ultrasonicate for 30 min to obtain solution A;

[0066] (2) Weigh 1.35 g of ferric chloride hexahydrate and dissolve it in 10 mL of 1 mol / L NaAc, stirring until it is completely dissolved to obtain a mixed solution B;

[0067] (3) Under stirring conditions, slowly add solution B dropwise into the above solution A and continue stirring for 12 h;

[0068] (4) The precipitate was collected by filtration, washed with distilled water and anhydrous ethanol, and dried in an oven at 70° C. for 18 h to obtain Fe-BDC.

[0069] Comparative Example 3

[0070] Fe-BDC was prepared by microwave DMF solvothermal method:

[0071] (1) Weigh 0.824 g of terephthalic acid (H2BDC) and dissolve it in 20 mL of DMF (content 99.5%) reaction solvent, and ultrasonicate for 30 min to obtain liquid A;

[0072] (2) Weigh 1.35 g of ferric chloride and dissolve it in 10 mL of DMF (content 99.5%), stirring until it is completely dissolved to obtain a mixed solution B;

[0073] (3) Add liquid B dropwise to liquid A under stirring and continue stirring;

[0074] (4) placing the mixed solution in a microwave chemical reactor under stirring and irradiating with a microwave power of 480 W for 8 minutes;

[0075] (5) Collect the precipitate by suction filtration, wash the precipitate with distilled water and anhydrous ethanol, and dry it in an oven at 70° C. for 18 h to obtain Fe-BDC.

[0076] Comparative Example 4

[0077] The Fe-BDC sample was prepared by microwave solvothermal method. The preparation method was similar to that in Example 1, except that the reaction solvent was NaOH aqueous solution.

[0078] Comparative Example 5

[0079] The Fe-BDC sample was prepared by microwave solvothermal method. The preparation method was similar to that in Example 1, except that the reaction solvent was Na2CO3 aqueous solution.

[0080] Comparative Example 6

[0081] The Fe-BDC sample was prepared in a similar manner to that of Example 1, except that the iron salt was 1.01 g of ferric chloride hexahydrate.

[0082] Comparative Example 7

[0083] The Fe-BDC sample was prepared in a similar manner to that in Example 1, except that the concentration of the NaAc aqueous solution was 0.1 mol / L.

[0084] Comparative Example 8

[0085] The Fe-BDC sample was prepared in a similar manner to that in Example 1, except that the microwave power was 160 W.

[0086] Application Example 1

[0087] 0.04 g of the samples prepared in Examples 1-8 and Comparative Examples 1-8 were added to 100 mL of a 50 mg / L tetracycline solution. After adsorption reached equilibrium, the solution mixed with the samples was placed in a microwave reactor, the microwave power was set to 480 W, and the microwave reaction was performed for 10 min.

[0088] The removal rates of tetracycline wastewater by the samples of Examples 1-8 are shown in Table 1.

[0089] Table 1

[0090]

[0091] Figure 1 The curves of the removal rate of tetracycline wastewater obtained by the samples of Example 1, Comparative Example 1 and Comparative Example 2 over time reflect the removal effect of the catalysts obtained by different preparation methods on tetracycline. It can be seen from the figure that the removal of tetracycline by Example 1 and Comparative Example 2 can reach more than 80%, and Example 1 has more adsorption sites and better removal effect on tetracycline. It shows that using NaAc as the reaction solvent, the microwave solvothermal method is both simple and efficient.

[0092] Figure 2The curves of the removal rate of tetracycline wastewater obtained by the samples of Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5 over time reflect the removal effect of the catalysts prepared by different solvents on tetracycline. It can be seen from the figure that Example 1 has a faster removal rate and better removal effect on tetracycline than Comparative Examples 3, 4 and 5. It shows that the targeted adjustment of acetate ions leads to the generation of defects, the number of active sites increases, and the catalytic performance is improved. Moreover, NaAc is non-toxic, non-corrosive and low in cost. Therefore, the microwave catalytic performance of Fe-BDC prepared with NaAc as the reaction solvent is better than that of other reaction solvents.

[0093] Figure 3 2 are XRD diagrams of the samples obtained in Example 1 and Comparative Example 1. It can be seen from the diagram that Example 1 has strong and sharp diffraction peaks at 2θ=17.8°, 25.6° and 28.3°, and no other impurity peaks are found. The sharp diffraction peaks prove that the prepared catalyst sample has good crystallinity.

[0094] Figure 4 The FT-IR images of the samples obtained in Example 1 and Comparative Example 1 show that the samples have similar structural vibrations because they are all constructed from the same trivalent metal center and carboxylic acid bridging ligand. -1 、1557cm -1 The characteristic diffraction peaks at 1393cm and 1394cm may be mainly derived from the vibration of the carboxylic acid group, representing the asymmetric stretching vibration and symmetric stretching vibration of the carboxylic acid part, respectively. -1 The characteristic peak at 3390cm -1 The wide band nearby is attributed to OH. 744cm -1 and 525cm -1 The absorption band at 3390 cm-1 is caused by the CH vibration bending of the terephthalic acid linker on the aromatic ring and the Fe-O vibration band. The presence of characteristic functional groups indicates that Fe-BDC was successfully synthesized by microwave solvothermal method. -1 The hydroxyl peak near 525 cm -1 The absorption peak at 1557cm becomes broader and stronger, indicating that there are more free hydroxyl groups and Fe-O bonds in the structure. -1 The absorption peak at the position blue-shifts, the stretching vibration shifts to low frequency, the spectral band becomes wider, and the intensity increases, indicating the formation of hydrogen bonds, which is conducive to the formation of defects.

[0095] Figure 5The removal rate of tetracycline wastewater obtained by the samples of Example 1, Example 2 and Example 3 varies with time. It can be seen from the figure that compared with Example 2-3, Example 1 has more adsorption sites, and the removal rate of 50mg / L tetracycline by microwave for 10min reaches 92.70%. According to Pearson's hard / soft acid-base theory, the metal organic framework constructed by ferric chloride (hard Lewis acid) and carboxylic acid ligand (hard Lewis base) is more stable.

[0096] Figure 6 The removal rate of tetracycline wastewater obtained by the samples of Example 1, Example 4 and Comparative Example 6 varies with time. It can be seen from the figure that compared with Comparative Example 6, Example 1 and Example 4 have more adsorption sites, and compared with Example 4, Example 1 has more adsorption sites and better tetracycline removal effect. Therefore, the molar ratio of iron salt to terephthalic acid is selected to be 1:1 to 2:1.

[0097] Figure 7 The removal rate of tetracycline wastewater obtained by the samples in Example 1, Example 5, Example 6 and Comparative Example 7 varies with time. - If the concentration is too low, the degradation rate of tetracycline is less than 40%. Therefore, the NaAc concentration is selected to be 1-5 mol / L.

[0098] Figure 8 The removal rate of tetracycline wastewater by the samples of Example 1, Example 7, Example 8 and Comparative Example 8 varies with time. If the microwave power is too low, the reaction may be incomplete; if the microwave power is too high, the structure may collapse. Therefore, the microwave power is selected to be 320-640W.

[0099] Application Example 2

[0100] 0.04 g of the Fe-BDC catalyst prepared in Example 1 was added to 100 mL of a 50 mg / L tetracycline solution. After adsorption reached equilibrium, the catalyst was placed in a microwave reactor, the microwave power was set to 480 W, and the microwave reaction was performed for 10 min. The catalyst after the microwave reaction was recovered, washed three times with deionized water and ethanol respectively, placed in an oven to dry, and then microwaved again with 100 mL of a 50 mg / L tetracycline solution. This was repeated twice. Results are shown in Fig. 9 The removal rates of tetracycline in three experiments after 10 min of microwave reaction were 92.70%, 83.64% and 74.56%, respectively, indicating that the catalyst has good stability.

[0101] It should be noted that the above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for synthesizing Fe-BDC microwave catalyst by microwave solvothermal method, characterized in that: The method comprises the following steps: (1) dissolving terephthalic acid in a NaAc aqueous solution to obtain liquid A; (2) dissolving iron salt in NaAc aqueous solution to obtain solution B; (3) Add liquid B dropwise to liquid A under stirring; (4) subjecting the mixed solution obtained in step (3) to microwave irradiation under stirring; (5) Collect the precipitate by filtration, wash, and dry to obtain a Fe-BDC microwave catalyst.

2. The method for synthesizing Fe-BDC microwave catalyst according to claim 1, characterized in that: In step (1), the concentration of the NaAc aqueous solution is 1 to 5 mol / L.

3. The method for synthesizing Fe-BDC microwave catalyst according to claim 1, characterized in that: In step (2), the iron salt is any one of ferric chloride hexahydrate, ferric nitrate nonahydrate, and ferric sulfate.

4. The method for synthesizing Fe-BDC microwave catalyst according to claim 1, characterized in that: In step (3), the molar ratio of the iron salt to terephthalic acid is 1:1 to 2:

1.

5. The method for preparing a synthetic Fe-BDC catalyst according to claim 1, characterized in that: In step (4), the power of the microwave irradiation is 320 to 640 W, and the time of the microwave irradiation is 1 to 60 min.

6. The method for synthesizing Fe-BDC microwave catalyst according to claim 1, characterized in that: In step (5), washing with deionized water and ethanol; The drying temperature is 40-90° C., and the drying time is 10-20 hours.

7. Use of the Fe-BDC microwave catalyst prepared by the method according to any one of claims 1 to 6 in the degradation of organic pollutants in wastewater by microwave irradiation.

Citation Information

Patent Citations

  • Preparation method of metal organic framework material and application of metal organic framework material in cyclohexyl hydroperoxide decomposition reaction

    CN105712867A

  • Preparation and application of efficient bimetallic Fe / Co-MOFs catalyst

    CN116726990A

  • Heavy metal chromium adsorption material as well as preparation method and application thereof

    CN117899832A

  • Preparation method and application of MIL-100 (Fe) material

    CN118930876A